Dialogical Self and Close Relationships: Looking for Ambivalences - Rosa, Catarina; Goncalves, Miguel (Studia Psychologica: Theoria et praxis, 2008)
According to Dialogical Self Theory (Hermans, 1996), the self is like a vocal society, i.e., it is populated by a community of I-positions or voices that are entitled to have an opinion and promote active discussions in order to make their viewpoint prevail. Having in mind the purpose of studying and deepening the interactions between these voices, a semi-structured interview was developed as an attempt to “give voice” to this multivocal assembly. In this interview, participants are invited to consider the significant dimensions they identify in their selves as characters and to narrate the possible dialogues between them – Dialogical Articulation Task, DAT (Duarte, Rosa & Gonçalves, 2006). Assuming that the relationship with a partner is one of the most central aspects in our relational life, we are interested in exploring the impact on the Dialogical Self of the changes that occur in couples throughout their relationship’s development (McGoldrick & Carter, 1982; Relvas, 1996). Two case studies are presented to illustrate the emergence of ambivalences and its regulation into self dynamics in the dialogues between the internal position that represents the couple’s relationship – termed by the participants ”I as a Relational” – and the remaining I-positions of the self-system.